Chemotherapeutic Effect on Ovarian Stroma and Tumor Cells Which Make Problem in Diagnosis and Staging of Tumor - Neda Nasirian; Khadigeh Elmizadeh (Iranian Society of Pathology, 2021)
Chemotherapy of ovarian tumors has some effects on morphology of stromal cells also residual tumoral cells which can cause problems in diagnosis of tumor type and staging of it .In some cases ,it can makes problem in diagnosis of residual epithelial tumor from other differential diagnosis such as spindle cell tumors like sarcoma.We had a case which had previouse chemotherapy. Her ovarian tumor had plump spindle cells with pleomorphism similar to spindle cell tumors.Finally ,in these cases ,Immuno histochemisteric study can differentiate correct diagnosis from differential diagnosis.